2020
DOI: 10.1186/s12966-020-01000-y
|View full text |Cite
|
Sign up to set email alerts
|

Scale-up of the Physical Activity 4 Everyone (PA4E1) intervention in secondary schools: 12-month implementation outcomes from a cluster randomized controlled trial

Abstract: Background: 'Physical Activity 4 Everyone' (PA4E1) was an efficacious multi-component school-based physical activity (PA) program targeting adolescents. PA4E1 has seven PA practices. It is essential to scale-up, evaluate effectiveness and assess implementation of such programs. Therefore, the aim is to assess the impact of implementation support on school practice uptake of the PA4E1 program at 12 and 24 months. Methods: A cluster randomised controlled trial, utilising a type III hybrid implementation-effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(48 citation statements)
references
References 29 publications
4
44
0
Order By: Relevance
“…Firstly, MM identi ed a list of adaptations between the e cacy and scale-up trial on physical activity practices, implementation support strategies and evaluation by triangulating data from a number of sources. The rst source was published PA4E1 research papers: the trial protocol (25), 12 and 24-month outcome papers (28, 32) and costeffectiveness paper for the e cacy trial (27); and the trial protocol (29), process evaluation protocol (31) and 12month practice outcome paper (30) for the scale-up trial. Secondly, we drew upon the trial registries for both trials.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Firstly, MM identi ed a list of adaptations between the e cacy and scale-up trial on physical activity practices, implementation support strategies and evaluation by triangulating data from a number of sources. The rst source was published PA4E1 research papers: the trial protocol (25), 12 and 24-month outcome papers (28, 32) and costeffectiveness paper for the e cacy trial (27); and the trial protocol (29), process evaluation protocol (31) and 12month practice outcome paper (30) for the scale-up trial. Secondly, we drew upon the trial registries for both trials.…”
Section: Methodsmentioning
confidence: 99%
“…The scale-up trial recruited 49 schools (24 program, 25 control) (30).…”
Section: Scale-up Trialmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously reported that the multimode implementation support strategies used in the PA4E1 scale-up trial increased the implementation of physical activity-promoting practices in lower socioeconomic secondary schools in New South Wales, Australia [32]…”
Section: Principal Findingsmentioning
confidence: 99%